The case of KACE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
On a typical weekday morning, the trading floor of the Kenya Agricultural Commodity Exchange at the Jamhuri Show Ground in Nairobi bustles with farmers, brokers and traders. Up on the boards, based on faxed and computer-delivered data, are the...